Improving the management of prison-based education staff through an examination of multi-agency psychological contracts - Mills, Julie (2006)
This study is set in the context of prison education. Contracted-out employment arrangements are becoming increasingly common and prison education services were put out to tender in 1993. Currently 27 contractors are responsible for education provision within the 138 state run prisons in England and Wales. One consequence of this employment arrangement is that prison-based education staff, working often exclusively within a prison, are employed by an organisation that is not necessarily geographically close to the prison in which they work. This study explores this employment relationship in the context of the psychological contract through investigating the contents of the psychological contracts of prison-based education staff perceived with their employer and with the host prison. Eighty-five semi-structured interviews, carried out across eleven prisons, used the critical incident technique to uncover prison-based education staff's perceptions of the obligations owed to them by their employer and by the host prison along with their perceptions of the obligations owed by themselves to their employer and to the host prison. Content analysis was carried out on the interview transcripts to reveal a hybrid psychological contract including relational and transactional items with both the employer and the host prison. The results suggest that prison-based education teams develop a strong sense of team identity and demonstrate their commitment to the team through pro-social behaviour in the form of team citizenship. There is also evidence that suggests prison-based education teams operate in a culture of intergroup differentiation which has implications for the way in which prison-education teams are managed. The academic contributions made by the study along with strategic implications for organisations employing prison-based education teams are discussed and recommendations for practice, both strategic and operational are made